MO034: Novel MUC1 variant identified by massively parallel sequencing explains interstitial kidney disease in a large Dutch family. (3rd May 2022) - de Haan, Amber; Eijgelsheim, Mark; Rump, Patrick; Van der Zwaag, Bert; Zivna, Martina; Kmoch, Stanislav; Bleyer, Anthony; Kidd, Kendrah; Van Eerde, Albertien M; Knoers, Nine; De Borst, Martin
Abstract: BACKGROUND AND AIMS: Chronic kidney disease (CKD) can be caused by a wide variety of systemic and renal disorders. In approximately 20% of patients, the cause of CKD remains unknown. Previous studies have shown that massively parallel sequencing (MPS) can be a valuable diagnostic tool in patients with unexplained CKD. Here, we describe a large family with kidney failure of unknown origin, in which we aimed to identify the primary renal disease diagnosis with MPS in a routine healthcare setting. METHOD: We conducted MPS in a large family in the Netherlands including six generations with documented kidney failure at young age. Affected individuals had a bland sediment and kidney biopsy revealed interstitial fibrosis in several family members. Whole exome sequencing followed by variant filtering and analysis based on the CKD-Y (CKD-young) gene panel (v18.1, 141 genes) was performed by the Genome Diagnostics Section of the University Medical Center Utrecht. RESULTS: MPS revealed a novel frameshift variant [c.326_350dup, p.(Ser119Profs*119), NM_001 204 286.1] in MUC1, which co-segregated with the renal phenotype in the family. This variant is positioned before the first variable number of tandem repeat (VNTR) domain of MUC1 and leads to a + 1 base frameshift in the open reading frame of the MUC1 mRNA. The predicted C-terminal amino-acid sequence of the resulting mutant protein is the same as the previously reported pathogenic cytosine insertions in the VNTR. Variants in MUC1 are associated with autosomal dominant tubulointerstitial kidney disease (ADTKD), which matches the clinical phenotype in this family. Immunohistochemical analysis in the index patient showed MUC1fs deposition in kidney tissue, confirming the diagnosis of ADTKD-MUC1. CONCLUSION: We report a novel frameshift mutation in MUC1 identified with MPS. This study highlights that MUC1 variants positioned before the first VNTR region can lead to ADTKD and that genetic testing in patients with suspected ADTKD-MUC1 should also include regions outside of the VNTR. Additionally, this study confirms the relevance of MPS as a tool to screen adult patients with early-onset kidney failure.